Breast cancer screening: knowledge and practices among women employees of a tertiary care hospital - Dyavarishetty, Padmavathi V.; Mistry, Megha S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Women employees, despite working in hospital do not undergo regular breast cancer screening due to poor awareness about the disease and the importance of undergoing regular breast cancer screening. The objectives of the study were to assess knowledge related to breast cancer disease, proportion of women ever screened for breast cancer and proportion of women with one or more risk factors for breast cancer. Methods: Observational descriptive cross-sectional study design was adopted to interview 88 women employees of a tertiary health care institute in Mumbai. A list of women employees other than a nurse or doctor, aged 30 years and above, working in the hospital or medical college was prepared. Women were sequentially approached and interviewed after obtaining an informed consent using a pre-tested, structured interview tool, till the sample size of 88 was reached. Data is presented using descriptive statistics like percentages, mean, standard deviation and standard error of mean. Results: Knowledge score of women was low with regard to symptoms and risk factors of breast cancer but high with regard to modalities of breast cancer screening. Overall proportion of women undergoing regular breast cancer screening by any of the methods (mammography, clinical breast examination or self-breast examination) is very poor. Knowledge levels greatly influenced the practice of breast cancer screening. Conclusions: Creating awareness about the disease and the need to undergo regular screening for breast cancer is required even for hospital employees.